The Influence of Loose Parts PjBL vs PBL and Learning Motivation on Students' Creative Thinking - Sabariah, Sabariah; Chotimah, Chusnul; Zaman, Akhmad Qomaru (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
This study aims to analyze the influence of learning models and learning motivation on the creative thinking abilities of first-grade elementary school students at Insan Cendekia Elementary School. The method used is an experiment with a 2x2 factorial design, involving 110 students from four randomly selected classes (A, B, C, and D). This study is included in the quasi-experimental category because it uses existing classes as research subjects. Data analysis was carried out using ANOVA with the help of SPSS version 27. Data collection instruments include a creative thinking test and a learning motivation questionnaire. The results showed that the PjBL model using loose parts and the PBL model had a significant influence on students' creative thinking abilities with an F value of 140.523 and a significance level of 0.000 (p <0.05). In addition, learning motivation also had a significant influence on students' creative thinking abilities (F = 11.151, p = 0.001). The interaction test between learning model and learning motivation showed an F-value of 11.072 with a significance level of 0.001, indicating a significant interaction effect. The conclusion of this study confirms the importance of both factors, specifically learning model and student learning motivation, in encouraging the development of creative thinking skills in early grade students. This finding underscores the need for adjustments to learning strategies by teachers, educational policies, and the development of learning theories that take both into account from the early stages of education.